From fat to facts: the potential of adipokine and insulin dosing in obese feline patients - Cernat, Laura; Daina, Sorana; Macri, Adrian (Frontiers in Animal Science, 2025)
The increasing prevalence of obesity in domestic cats is closely linked to the emergence of diabetes mellitus, highlighting the need for early diagnostic tools. Obese cats typically show elevated leptin and reduced adiponectin levels—markers associated with early insulin resistance. Leptin resistance and compensatory hyperinsulinemia further reflect early metabolic dysfunction. These endocrine changes mirror those seen in humans and dogs, suggesting shared mechanisms across species. Incorporating these biomarkers into clinical practice could aid early risk stratification and preventive care. However, standardized reference ranges and cost-effective assays are still needed. This review assesses the predictive value of adiponectin, leptin, and insulin in identifying diabetes risk in obese cats.